2022
DOI: 10.1021/acsomega.2c05148
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical and Petrological Characterization of the Early Eocene Carbonaceous Shales: Implications for Oil and Gas Exploration in the Barmer Basin, Northwest India

Abstract: Carbonaceous shales of the Early Eocene Dharvi/Dunger Formation in the onshore Barmer Basin, northwest India were studied for the first time by integrating geochemical and organic petrological analyses. The carbonaceous shales of the Early Eocene Dharvi/Dunger Formation are characterized by a higher organic carbon content (TOC) of >10 wt % and consist mainly of a mixture of organic matter of types II and III kerogen, with exhibited hydrogen index values ranging between 202 and 292 mg HC/g TOC. The dominance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Sofer 39 and Summons et al 42 reported that the δ 13 C values mentioned above are a means to distinguish terrestrial from the marine OM input. Low δ 13 C of heaver values (less negative) suggest a terrigenous origin, while high and moderate of lighter δ 13 C values (more negative) come from marine OM (i.e., algae and microbes). 39 As a result, the examined shale samples appear to be receiving high contributions from the terrigenous OM, as evidenced by the low δ 13 C values (Table 2).…”
Section: Carbon Stable Isotope ( δ13 C)mentioning
confidence: 99%
See 1 more Smart Citation
“…Sofer 39 and Summons et al 42 reported that the δ 13 C values mentioned above are a means to distinguish terrestrial from the marine OM input. Low δ 13 C of heaver values (less negative) suggest a terrigenous origin, while high and moderate of lighter δ 13 C values (more negative) come from marine OM (i.e., algae and microbes). 39 As a result, the examined shale samples appear to be receiving high contributions from the terrigenous OM, as evidenced by the low δ 13 C values (Table 2).…”
Section: Carbon Stable Isotope ( δ13 C)mentioning
confidence: 99%
“…Organic-rich sediments such as oil shale and gas shale are the key hydrocarbon resources worldwide and have recently become important global exploration targets. , These fine-grained sedimentary rocks are of great interest owing to their organic-rich matter and have drawn attention as a source rock for conventional and unconventional gas and oil over the past 30 years. However, both marine and continental organic-rich shale sediments have been successfully explored and developed worldwide, showing valuable source rocks for generation of significant amounts of hydrocarbon during thermal maturation, and they have been proved by several studies. …”
Section: Introductionmentioning
confidence: 99%
“…These basins were developed by intracratonic sedimentation and are mostly located in the western part of Rajasthan. These basins include a sizable lignite resource that is mostly composed of thick organic-rich black shale partings, which are mainly found in the Paleocene-Eocene sequences [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Th sins were developed by intracratonic sedimentation and are mostly located in the w part of Rajasthan. These basins include a sizable lignite resource that is mostly com of thick organic-rich black shale partings, which are mainly found in the Paleoce cene sequences [17,18]. The Palana Formation has attracted the attention of academia and exploration companies due to the presence of OM-bearing black shale sediments as superior source rocks and hydrocarbon generation potential.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have provided evidence of the potential of coal and carbonaceous shale sediments as source rocks for oil and gas generation in various regions, including Brunei (Osli et al, 2022), Malaysia (Abdullah et al, 2017;Hakimi et al, 2013), Yemen (Alaug et al, 2013;Hakimi et al, 2013), New Zealand (Amansure, 2014;Jumat et al, 2018;Sykes et al, 2014), Hungary (Körmös et al, 2020), India (Kumar et al, 2022;Singh et al, 2020) and Turkey (Karayigit et al, 2021).…”
mentioning
confidence: 99%